Emergence and control of epidemic meningococcal meningitis in sub-Saharan Africa. (2nd January 2017) - Mohammed, Idris; Iliyasu, Garba; Habib, Abdulrazaq Garba
Abstract: For more than a century, meningitis epidemics have regularly recurred across sub-Saharan Africa, involving 19 contiguous countries that constitute a 'meningitis belt' where historically the causative agent has been serogroup A meningococcus. Attempts to control epidemic meningococcal meningitis in Africa by vaccination with meningococcal polysaccharide (PS) vaccines have not been successful. This is largely because PS vaccines are poorly immunogenic in young children, do not induce immunological memory, and have little or no effect on the pharyngeal carriage. Meningococcal PS–protein conjugate vaccines overcome these deficiencies. Conjugate meningococcal vaccine against serotype A (MenAfriVac) was developed between 2001 and 2009 and deployed in 2010. So far, 262 million individuals have been immunized across the meningitis belt. The public health benefits of MenAfriVac have already been demonstrated by a sharp decline in reported cases of meningococcal disease in the countries where it has been introduced. However, serogroup replacement following mass meningitis vaccination has been noted, and in 2015 an epidemic with a novel strain of serogroup C was recorded in Niger and Nigeria for the first time since 1975. This has posed a serious challenge toward elimination of meningococcal meningitis epidemics in the African. For an effective control of meningococcal meningitis in the African meningitis belt, there is a need for an effective surveillance system, provision of rapid antigen detection kits as well as affordable vaccine that provides protection against the main serogroups causing meningitis in the sub-region.